Contribution to the lichen biota of Slovenia XII. Some lichens from Logarska dolina - Bilovitz, Peter Othmar (2010)
A list of 94 species is presented including Bacidia subacerina and Lopadium disciforme as new for Slovenia and Bilimbia accedens, Lecanora leptyrodes, Megalaria grossa, Mycobilimbia epixanthoides, Rinodina efflorescens, and Sclerophora peronella as new for the alpine phytogeographical region of Slovenia.